Unveiling Opinions: Exploring the Public’s View on Clinical Autopsies - Ramlah Naz, Mehreen Fatima, Syed Inamul Rehman, Raffat Rasool, Shahla Imran, Farah Waseem, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Clinical autopsy is an invaluable tool useful to identify causes of death and to uncover unknown and unexpected diseases which aids in raising awareness of common and rare diseases in a community. Clinical autopsy is essential to study pattern of morbid diseases that aids in formation of effective healthcare policies. Aim: To investigate the views of the general public on clinical autopsies in order to determine general conceptions and misconceptions that may aid in further a discussion and investigations. Methodology: This prospective cross-sectional study was conducted at Department of Forensic Medicine, Dow International Medical College, Dow University of Health Sciences Karachi Pakistan from October 2022 till March 2023. Data was collected from 300 participants using a 15-item questionnaire distributed to general population from various parts of Karachi selected by convenient sampling. Results: 46% were aware of term clinical/medical autopsy. 77% acknowledged medical and social role of clinical autopsies. Less than 50% could differentiate between clinical and medico legal autopsy. 50% are of the opinion that autopsy should not be conducted in natural deaths. 55% and 64% of the participants were of the opinion that clinical autopsy can improve future lives of people and provide diagnostic and curative strategies respectively. Participants of the study were unsure about the Islamic perspective of autopsy. 57% agreed to give consent for autopsy in society’s best interest. Conclusion: The large majority is uncertain about autopsy given their religious and personal views but it also reveals many acknowledge its possible utility in medicine and in bereavement process. Therefore, despite lack of research and public discourse, it provides us with data that may encourage and aid further research and discussion about acceptance of autopsy as a viable diagnostic tool. Keywords: Autopsy, Clinical autopsy, Medical autopsy, Pakistan